Investigation on the effect of different levels of peat sampling on oedometer test - Belinda Anak, Mason (Universiti Malaysia Sarawak (UNIMAS), 2008)
Peat which is considered as a problematic soft soil due to its high water content and compressibility and low bearing capacity. Generally, higher percentage of moisture and organic content are likely to influence the consolidation and settlement of the peat soil. This study was focused on the effect of different levels of peat sampling on one-dimensional consolidation test. Oedometer consolidation test are conducted for samples taken from Matang at different level of depths. Several parameters such as coefficient of consolidation, Cv, compression index, C, and the coefficient of volume compressibility, mv were determined. Apart from that, the physical and chemical properties were also determined. The result shows that the coefficient of consolidation, Cv and the coefficient of volume compressibility, mv show decreasing value when subjected to increment of consolidation pressure with time. Meanwhile, the compression index, C is found to have a good correlation between moisture content and void ratio. However, the properties and characteristics of peats vary with their depths, locations and conditions of that particular area.